Si film electrodes containing surface-modified Cu current collectors prepared by a low temperature oxidation-reduction process. (October 2016) - Cho, Gyu-Bong; Jeong, Jae-Seung; Im, Yeon-Min; Choi, Hyon-Kwang; Noh, Jung-Pil; Kim, Jae-Kwang; Ahn, Hyo-Jun; Nam, Tae-Hyun; Kim, Ki-Won
Abstract: A low-temperature oxidation-reduction process was used to modify the surface of a Cu current collector (foil) for a Si film electrode. The surfaces of the modified Cu foils were investigated under various oxidation-reduction conditions, and the electrochemical properties of Si film electrodes containing the surface modified foils were evaluated. Various nanostructures were found to have formed on the surface; for example, Cu(OH)2 needles, CuO flowers, and CuO plates formed on Cu-foil surfaces oxidized at 313 K for 1, 10, and 30 min, respectively. Furthermore, these nanostructures were transformed to coral-like Cu2 O structures after reduction at 673 K. The amount of Cu2 O and the surface roughness decreased on increasing reduction time. The Si film electrode containing a Cu foil reduced for 6 h showed the best electrochemical performance (83.5% of the initial efficiency and 74.8% of capacity retention) due to the small amount of Cu2 O and the formation of coral-like structures. Highlights: Surface-modified Cu foil was made by a low-temperature oxidation-reduction process. Nanostructures of needle, flower, plate shapes were formed after oxidation process. Coral-like structure was formed after reduction process. Si film electrode with Cu foil reduced for 6 h demonstrated the best properties.